THE VALUES OF EDUCATION IN THE NOVELS âSERIALS OF ANAK-ANAK MAMAKâ BY TERE LIYE A STUDY OF STRUCTURAL SEMIOTICS - Madusari, Endah Ariani; Emzir, E (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2015)
The purpose of this study is to discover the values of education in the novels "Series of Anak-anak Mamak" by Tere Liye. The novels are more appropriately analyzed by using structural semiotic studies because the sentences used in the author of four novels consist of language styles and idioms. "Series of Anak-anak Mamak" also contain quite a lot of educational values. This study used a qualitative approach with content analysis method. The focus of the research is: the value of education in terms of structural and semiotic theories contained in the novels "Series of Anak-anak Mamak". The finding of this study is a description of the values of education in the novels entitled "Eliana", "Pukat", "Burlian" and "Amelia" by using a semiotic approach. The whole chapters in the four novels contain the values of education when viewed from the structural theory. Total percentage of the values of education contained in the four novels are: (1) honesty amounted to 18.33%, (2) fidelity amounted to 12.50%, (3) tolerance amounted to 8.33%, (4) confidence amounted to 47.50%, and (5) affection amounted to 13.33%. Semiotic studies in this novel are based on the styles of language and idioms, included connotative meanings. The whole chapters in the novel contain the values of education from the semiotic standpoint. Total percentage of the values of education from the semiotic standpoint of the four novels are: styles of language amounted to 57.25% and idioms amounted to 42.75%.